Systems, software and service process improvement 18th European conference, EuroSPI 2011, Roskilde, Denmark, June 27-29, 2011. Proceedings - Pries-Heje, Jan.; Messnarz, Richard; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the 18th EuroSPI conference, held in Roskilde, Denmark, in June 2011. The 18 revised full papers presented together with 9 key notes were carefully reviewed and selected. They are organized in topical sections on SPI and assessments; SPI and implentation; SPI and improvement methods; SPI organization; SPI people/ teams; SPI and reuse; selected key notes for SPI implementation.
Keywords: Electronic books; Computer science; Software engineering; Information systems; Information Systems